Supplement to: Fibre Optic Distributed Temperature Sensing Behind Casing: Data From Geothermal Well HE-53, Hellisheiði Geothermal Field, SW Iceland - Reinsch, Thomas; Henninges, Jan (Deutsches GeoForschungsZentrum GFZ, 2012)
Abstract Reinsch et al. (2013) describe the installation of a novel fibre optic cable behind the anchor casing of the geothermal well HE-53, Hellisheiði geothermal field, SW Iceland. Within this data publication, DTS temperature data, acquired together with optical time domain reflectometry (OTDR) data during three different field campaigns are presented. Data have been acquired during the installation in spring 2009, during the onset of a production test in summer 2009 and after a 8.5 month shut-in period in summer 2010.